KAIN SEBAGE - Era Paraswati (Institut Seni Indonesia Yogyakarta, 2014)
Sebage fabric is one of the typical fabric manufacturing techniques Lampung are madewith batik techniques. Along with the development of batik in Indonesia. Fabric Sebagereintroduced in 1999 by Governor Drs. Oemarsono, at that time. Sebage fabric used fortraditional ceremonial purposes. Sebage fabrics grouped into two types, namely Sebage fabricBalak (Large) and Sebage fabric Lunik (Small). Keywords: Fabric, Sebage, Batik, Lampung Kain Sebage merupakan salah satu kain khas daerah Lampung yang teknikpembuatannya dibuat dengan teknik membatik. Seiring dengan perkembangan batik diIndonesia. Kain Sebage diperkenalkan kembali pada tahun 1999 oleh Gubernur Drs.Oemarsono, pada saat itu. Kain sebage digunakan untuk kepentingan upacara adat. Kainsebage dikelompokan menjadi 2 jenis yaitu kain sebage Balak (Besar) dan Kain Sebage Lunik(Kecil). Kata Kunci: Kain, Sebage, Batik, Lampung